Wilson and Gould: The Engagement of the Sciences and the Humanities - Carbonell, Curtis D. (Mediterranean Journal of Social Sciences, 2011)
This article looks at two evolutionary theorists, E.O. Wilson and Stephen Jay Gould, whose differing notions of consiliencereflect a fundamental divide on the nature of the relationship between the sciences and the humanities. This article reads Wilson as seeinga need for the social sciences and humanities to move toward the reductive methods and principles of the natural sciences. It charts a briefintellectual history of Wilson’s argument. This article presents Gould and his wish to approach the sciences and the humanities asindependent domains of investigation. At issue between Gould and Wilson is the weight given to analysis and synthesis. Wilson is keento argue that both methods, the analytical breaking down of parts via reduction and the synthetic rebuilding of knowledge, are importantin his endeavor of consilience. This article argues that reduction is weighted heavier by Wilson (if only because the sciences are better at it).However, Gould’s approach values the sort of synthesis that can also be found in the humanities, predicated on the basic understandingthat the parts cannot always describe the whole. In this way, the synthetic move upward from analysis is considered to be a differentprocess altogether. Thus, Gould looks to the humanities as an example of how this might be done. In such a way, Gould promotes anequal engagement by both domains instead of marginalizing one at the benefit of the other.